Cost-benefit analysis to support decarbonization scenario for 2030: A case study in Italy. (February 2020) - Sofia, Daniele; Gioiella, Filomena; Lotrecchiano, Nicoletta; Giuliano, Aristide
Abstract: Mitigation strategies towards progressive decarbonization of the energy system are a valid approach to slow environmental pollution yielding social benefits, as established from National Energy and Climate Plan (NECP). The first objective is the increase of energy efficiency within 2030 by promoting the use of renewable energy and the electrification of consumption in other sectors (household and transport). Cost-benefit analysis (CBA) is an analytical tool to evaluate investments and support policy decisions for society's welfare. The paper aims to assess how CBA can be used to quantify the costs and related social benefits in different sectors (energy, transport and household) if the decarbonization scenario is applied in Italy in 2030. Overall, our findings show positive benefits obtained with the adoption of different mitigation strategies for all sectors. These results can provide significant support to decision-makers in the implementation of decarbonization scenario in Italy scheduled for 2030. Highlights: Cost-Benefit analysis to validate the decarbonization scenario in Italy for 2030. Mitigation strategies in energy, transport and household sectors are investigated. Benefit/cost ratios are positive for all strategic measures recommended. Reductions in air pollution emissions and human health impacts are possible. Findings support policy-makers in the adoption of decarbonization scenario in Italy.